File encryption based on reduced-round AES with revised round keys and key schedule - Edjie Malonzo De Los Reyes; Ariel M. Sison; Ruji P. Medina (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The continuing advancement of technology had provided security issues in protecting the confidentiality of information. The need to protect unauthorized access of a third party is warranted.  In this paper, the reduced-round modified AES with revised round keys and key schedule is proposed to ensure file confidentiality.  The modifications to the AES cipher round was the reduction of the round iterations from 10 to 6, and additional key permutations were added in between states; while in the key schedule, additional byte substitution process was appended.  Time and throughput were utilized to measure the performance of the application's encryption/decryption process; while the avalanche effect and randomness tests were used to measure the security of the modified AES algorithm.  The results of evaluations have shown that the encryption and decryption time have improved by 1.27% and 1.21% respectively while the throughput has similarly improved by 1.29% and 3.19% for both encryption and decryption respectively.  Whereas the avalanche effect of the modified AES was 50.06% which was more than the ideal value of 50% and it was also better than the standard AES which was 49.94% using the sample dataset.  Finally, all the ciphertext outputs of the modified AES passed the randomness tests.